Early and Effective Diagnosis of Sepsis Using Flow Cytometry - Verma, Pratima; Singh, Anurag; Kushwaha, Rashmi; Yadav, Geeta; Verma, Shailendra P.; Singh, Uma S.; Reddy, Himanshu D.; Agarwal, Avinash (Journal of Laboratory Physicians, 2022)
Objective Sepsis is a major global health issue due to its high death and morbidity rates. To avoid the negative effects of sepsis and decrease mortality, it is vital to diagnose and treat it as soon as possible. Blood cultures can take up to 2 days to give result, and they are not always reliable. According to recent studies, neutrophil CD64 expression might be a sensitive and specific option for assessing sepsis. This study aimed to evaluate the diagnostic performance of a flow cytometry analysis for the expression of neutrophil CD64 in sepsis and its comparison with other standard tests in a tertiary care center.Materials and Methods Prospective analysis on 40 blood samples from suspected sepsis patients admitted to intensive care units with criteria for the systemic inflammatory response syndrome on presentation was performed for expression of neutrophil CD64, C-reactive protein, procalcitonin, and complete blood count. Ten healthy volunteers were also enrolled in this prospective study. The laboratory results were compared in different groups.Results The neutrophil CD64 had the highest diagnostic value to differentiate between patients of sepsis and nonsepsis groups with a sensitivity of 100% (95% confidence interval [CI]: 77.19–100%) and 100% (95% CI: 55.32–86.83%); specificity of 90.00% (95% CI: 59.58–99.49%) and 87.24% (95% CI: 66.69–99.61%); and likelihood ratio of 10.00 and 7.84, respectively.Conclusion The neutrophil CD64 expression provides a more sensitive, specific, and novel marker for the early detection of sepsis in critically ill patients.
Keywords: CD64; sepsis; biomarker; flow cytometry; intensive care unit